HATS-15b and HATS-16b: Two Massive Planets Transiting Old G Dwarf Stars *The HATSouth network is operated by a collaboration consisting of Princeton University (PU), the Max Planck Institute für Astronomie (MPIA), the Australian National University (ANU), and the Pontificia Universidad Católica de Chile (PUC). The station at Las Campanas Observatory (LCO) of the Carnegie Institute is operated by PU in conjunction with PUC, the station at the High Energy Spectroscopic Survey (H.E.S.S.) site is operated in conjunction with MPIA, and the station at Siding Spring Observatory (SSO) is operated jointly with ANU. Based in part on observations performed at the ESO La Silla Observatory in Chile, with the Coralie and FEROS spectrographs mounted on the Euler-Swiss and MPG 2.2 m telescopes, respectively. This paper includes data gathered with the 6.5 m Magellan Telescopes located at Las Campanas Observatory, Chile. Based in part on data collected at Keck Telescope. Observations obtained with facilities of the Las Cumbres Observatory Global Telescope are used in this paper. (10th June 2016) - Ciceri, S.; Mancini, L.; Henning, T.; Bakos, G.; Penev, K.; Brahm, R.; Zhou, G.; Hartman, J. D.; Bayliss, D.; Jordán, A.; Csubry, Z.; de Val-Borro, M.; et al.
Abstract: We report the discovery of HATS-15 b and HATS-16 b, two massive transiting extrasolar planets orbiting evolved (∼10 Gyr) main-sequence stars. The planet HATS-15 b, which is hosted by a G9 V star ( V = 14.8 mag), is a hot Jupiter with mass of 2.17 ± 0.15 M J and radius of 1.105 ± 0.040 R J, and it completes its orbit in about 1.7 days. HATS-16 b is a very massive hot Jupiter with mass of 3.27 ± 0.19 M J and radius of 1.30 ± 0.15 R J ; it orbits around its G3 V parent star ( V = 13.8 mag) in ∼2.7 days. HATS-16 is slightly active and shows a periodic photometric modulation, implying a rotational period of 12 days, which is unexpectedly short given its isochronal age. This fast rotation might be the result of the tidal interaction between the star and its planet.